Women and men facing lexical innovation - Cañete González, Paola (Colombian Applied Linguistics Journal, 2017)
Over the last few decades, the gender variable has been investigated in terms of linguistic variation. A number of studies (mainly phonological in nature) have been carried out which have generated preliminary conclusions such as women are more conservative and use more standard forms of language than men or that men are more innovative than women (Chambers, 2009; Labov, 1994). Generally, we are aware that new words are created every day which is indicative of the dynamism of languages and the changes taking place in a given society. The study of new lexical entities, called neologisms, allows us to understand how language speakers adapt to social changes. The two issues mentioned above are our main motivation to conduct this investigation which will be based on a linguistic approach with a focus on neology. Hence, this paper focuses on Spanish neological units produced by women and men as found in contemporary newspaper articles and blogs through a qualitative analysis of neologisms used by women and men as well as a qualitative analysis of the formation of these neologisms. Finally, we present a comparison between the results obtained in both types of text.